2019
DOI: 10.30543/8-2(2019)-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Blue Ocean Strategy in Achieving a Competitive Advantage: An Empirical Study on Al - Rajhi Bank - KSA

Abstract: The aim of this research is to identify the extent to which the banking sector in Saudi Arabia has adopted the strategy of the Blue Ocean in enhancing competitive advantage. The study measured the effect of the blue ocean strategy dimensions (Eliminate, Reduce, Raise, Create) on competitive advantage. The research collected 96 surveys from employees from Al Rajhi Bank in Riyadh. The results of the factor analysis showed that the strategy of the Blue Ocean affects competitive advantage. The regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Eliminate is identifying elements or activities in the school that can be eliminated because they are not important or do not contribute significantly to the unique value proposition, service and quality (Shared, 2019). Nature schools eliminated the uniform dress code as required in schools in general.…”
Section: Discussionmentioning
confidence: 99%
“…Eliminate is identifying elements or activities in the school that can be eliminated because they are not important or do not contribute significantly to the unique value proposition, service and quality (Shared, 2019). Nature schools eliminated the uniform dress code as required in schools in general.…”
Section: Discussionmentioning
confidence: 99%
“…It focuses on the creation of new demand, the capture of unexplored market spaces, and the domination of restructured industry boundaries (Karaoulanis, 2018). Empirical evidence from diverse studies reaffirms the pivotal role of these strategies in achieving sustainable and improved performance, including market share and production expansion (Shared, 2019). For organizations, the Blue Ocean Strategy offers a strategic path to performance and competitive advantage within their respective industries (Utami, 2021).…”
Section: Blue Ocean Strategy and Firm Performancementioning
confidence: 99%
“…Yet, in the end, the achievement of BOS can be considered a competitive advantage. few studies in the past were related to the implementation of the BOS with the achievement of competing superiority such as Shared (2019) in Saudi Arabia and Bataineh and Alomyan in Jordan.…”
Section: Blue Ocean Strategy and Competitive Advantagementioning
confidence: 99%
“…According to Shared (2019) the four-dimensional influence of the BOS referred to as The Four Action Framework on competing excellence. The author found that BOS's dimensions are positively influence the performance of Al-Rajhi Bank of Saudi Arabia.…”
Section: Blue Ocean Strategy and Competitive Advantagementioning
confidence: 99%
See 1 more Smart Citation